2020
DOI: 10.3389/fendo.2020.00538
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Melanocortin-4 Receptor Pharmacology by Two Isoforms of Melanocortin Receptor Accessory Protein 2 in Topmouth Culter (Culter alburnus)

Abstract: Melanocortin-4 receptor (MC4R) plays important roles in regulation of multiple physiological processes, and interaction of MC4R and melanocortin receptor accessory protein 2 (MRAP2) is suggested to play pivotal role in energy balance of vertebrates. Topmouth culter (Culter alburnus) is an economically important freshwater fish in China. Herein we cloned culter mc4r, mrap2a, and mrap2b. Culter mc4r consisted of a 981 bp open reading frame encoding a protein of 326 amino acids. qRT-PCR revealed that mc4r, mrap2a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 61 publications
11
41
1
Order By: Relevance
“…This finding indicates that as in chickens, ACTH, α-MSH, and β-MSH can function as the ligands for tilapia MC4R [ 5 ]. Our finding partly agrees with recent findings in spotted gar, tilapia, topmouth culter, and zebrafish, showing that MC4R could be activated by mammalian α-MSH (or NDP-α-MSH) and ACTH 1-24 /ACTH 1-39 with similar potencies [ 3 , 15 , 41 , 42 ]. Interestingly, in the presence of MRAP2b, the sensitivity and selectivity of MC4R for ACTH 1-40 increase by ≈8-fold (EC 50 : 0.246 nM vs. 0.032 nM), while its sensitivity to α-MSH and β-MSH shows little or no change ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding indicates that as in chickens, ACTH, α-MSH, and β-MSH can function as the ligands for tilapia MC4R [ 5 ]. Our finding partly agrees with recent findings in spotted gar, tilapia, topmouth culter, and zebrafish, showing that MC4R could be activated by mammalian α-MSH (or NDP-α-MSH) and ACTH 1-24 /ACTH 1-39 with similar potencies [ 3 , 15 , 41 , 42 ]. Interestingly, in the presence of MRAP2b, the sensitivity and selectivity of MC4R for ACTH 1-40 increase by ≈8-fold (EC 50 : 0.246 nM vs. 0.032 nM), while its sensitivity to α-MSH and β-MSH shows little or no change ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we proved that tilapia MC4R also has a strong basal constitutive activity, as monitored by dual-luciferase reporter assay. Moreover, we found that MRAP2b can inhibit the basal constitutive activity of tilapia MC4R, as recently reported in orange-spotted grouper, topmouth culter, and tilapia [ 15 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 86%
“…MC4R has been investigated in several non-mammalian vertebrates including ectotherm fish, such as goldfish [ 25 ], rainbow trout [ 26 ], spotted scat [ 27 ], grass carp [ 28 ], ricefield eel [ 29 ], orange-spotted grouper [ 30 ], and topmouth culter [ 31 ]. Similar to mammalian MC4Rs, teleost MC4R is also involved in regulating food intake and maintaining energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…MRAP2 and its modulatory role on MC4R have also been studied in several fishes. Different from mammals, some teleosts, such as zebrafish and topmouth culter, possess two isoforms of MRAP2 [ 35 , 36 , 37 ], while other lower vertebrates including tilapia, sea lamprey, and grouper, have only one [ 30 , 38 , 39 ], suggesting that the phylogenetic process in fish may be more complex than in mammals. In addition, MRAP2 has different effects on MC4R expression, ligand binding, and signaling in different fishes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation